Cystic Artery: Anatomic Variations - Cedrón, Hugo (1996)
This study addresses the controversial issue of the biliary tract anatomy: the cystic artery. Finding its origin and topographic relations will allow us not to damage it and perform an easy ligature, when necessary.The study was carried out at the Anatomy Amphitheatre Facultad de Medicina de San Fernando; the sample was composed of 20 corpses and the study was descriptive. We found various origins for the cystic artery; 15 cases from the right hepatic artery (75%), 1 case from the medium hepatic artery (5%) and 4 cases (20%) directly from the common hepatic artery. In 17 cases (85%) the artery was single; in 3 cases (15%) it was duplicate. When we related the Calot's triangle with the origin of the artery, we found that in 13 cases (65%) the origin was within the triangle; in 7 cases (35%) the origin was outside the triangle; 4 cases (20%) in front of the hepatic duct, and in 3 it was behind the cystic duct. In 18 cases (90%) it was within the triangle and in 2 cases (10%) it was outside. The cystic artery was bifurcated at the gallbladder's cervix in 10 cases (43.4%), before it in 8 cases (34.9%). The artery was not bifurcated and ended as a direct branch in 5 cases (21,7%). The artery's length ranged from 4.48 to 42.60 mm, averaging 48.35 mm. The results show a great morphologic variations that must be considered on surgical interventions of the biliary region.